The Influence of the PBL Model to Student Learning Outcomes on Heat and its Transfer Concepts - Sri Maulina Otoluwa; Ritin Uloli; Tirtawaty Abdjul; Mursalin; Abdul Haris Odja; Nova Elysia Ntobuo (Postgraduate, University of Mataram, 2024)
This research aims to determine the influence of the Problem-Based Learning (PBL) model to student learning outcomes on heat and transfer concepts by using experimental research, with the research design being One Group Pretest-Posttest Design. The population of this study was class VII students of SMP Negeri 5 Gorontalo. The sample consists of 3 classes, namely experimental class, replication 1, and replication 2, with the sampling technique being Cluster Random Sampling. The instrument of research used was a learning outcomes test in the form of a pretest-posttest to see student learning outcomes. Then, the data was analyzed using descriptive and inferential statistics, including normality tests, hypothesis tests, and n-gain analysis. The average score for class VII students is greater than the Criteria for Achieving Learning Goals, shown by an average score for the experimental class of 82.25, replication 1 of 79.94, and replication 2 of 79.04, compared to the Criteria for Achieving Learning Goals of 70. Based on the hypothesis testing criteria for the class, experimental Tcount 7.036 is greater than Ttable 2.035, replication 1 Tcount 6.684 is greater than Ttable 2.035, and replication 2 Tcount 5.824 is greater than Ttable 2.035 so it stated Tcount is more prominent than Ttable. This can be interpreted that the PBL model influences student learning outcomes.